Low Blood Lead Levels and educational achievement in 7-8 year old children in the Community of Madrid (Spain) - José María Ordóñez Iriarte; Manuel Ignacio Aparicio Madre; José Jesús Guillén Pérez; María José Martínez García (Revista de Salud Ambiental, 2013)
Background: Lead affects the behavioral and cognitive functions of children. The current lead safety level for avoiding these adverse effects is still controversial.